General issues in the education of adolescents - Urdan, Timothy C.; Pajares, Frank (Emerald Publishing Limited : Information Age Publishing, 2001)
In this inaugural volume, we solicited chapters from leading scholars in a variety of fields related to education. Our aim was to provide a broad overview of several of the most pressing concerns regarding the education of adolescent students. The volume begins with an historical perspective from Barbara Finklestein, who provides background regarding America's changing perceptions of adolescence as a developmental period and how American society has approached the task of educating this age group over time. This is followed by chapters from Carol Midgley and from Sanford Dornbusch and Jeanne Kaufman regarding the organization, purpose, and function of schools designed to serve early and late adolescents. Midgley uses an achievement goal theory lens to analyze middle level schools; Dornbusch and Kaufman consider senior high schools, adopting a more sociological perspective.
Keywords: Education, Secondary -- United States.; High school teaching -- United States.; Youth -- United States.; Education -- Schools -- Levels -- Secondary.; Secondary schools.; elektronické knihy; electronic books